Forage potential of experimental soybean lines (Glycine max) - Garay-Martínez , Jonathan Raúl; Maldonado-Moreno, Nicolás; Ascencio-Luciano, Guillermo; Joaquín-Cancino, Santiago; Bautista-Martínez , Yuridia; Granados-Rivera, Lorenzo Danilo (Ecosistemas y Recursos Agropecuarios, 2021)
Five experimental lines (H15-0625, H15-0249, H14-0307, ​​H14-0496 and H10-0556) and two commercial varieties (Huasteca 200 and Huasteca 300) of soybean [Glycine max (L.) Merr.] Were evaluated at 77, 91 and 105 days after sowing (DAS). The variables were crop growth rate (CGR), total dry matter (TDM), crude protein (CP), total digestible nutrients (TDN) and metabolizable energy (ME). A completely randomized design with four repetitions (Tukey; ɑ=0.05) was used. Lines H10-0556 and H14-0496, presented the highest (p